2019
DOI: 10.2139/ssrn.3407825
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Fiscal Decentralization on Publicly Provided Services and Labor Markets

Abstract: This paper studies how fiscal decentralization affects local services. It exploits a 1993 reform that increased the fiscal autonomy of Italian municipalities by introducing a local property tax. The identification leverages cross-municipal variation in the degree of decentralization stemming from Allied bombings during WWII. Decentralization reduced overall spending, but expanded municipal services, such as nursery schools. These effects are larger in areas with higher political competition. The paper also inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Kelkar (2005) claimed that female poverty is mainly caused by underemployment that, in turn, worsen the disparity in gender relations in South Asia. Bianchi et al (2019) found that fiscal decentralization is positively associated with female employment in Italy. Hence improving the components of gender parity through fiscal decentralization, improve the overall gender parity index.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Kelkar (2005) claimed that female poverty is mainly caused by underemployment that, in turn, worsen the disparity in gender relations in South Asia. Bianchi et al (2019) found that fiscal decentralization is positively associated with female employment in Italy. Hence improving the components of gender parity through fiscal decentralization, improve the overall gender parity index.…”
Section: Resultsmentioning
confidence: 96%
“…A large body of literature has investigated the impact of fiscal decentralization on different socioeconomic indicators e.g. economic growth (Cantarero & Gonzalez, 2009;Leonov et al, 2012;Martinez-Vazquez & McNab, 2006), health and education (Asfaw et al, 2007;Stotsky, 2019), income inequality (Boex et al, 2006;Grisorio & Prota, 2015) and employment (Bianchi et al, 2019;Martinez-Vazquez & Yao, 2009). The empirical literature shows that micro and macroeconomic indicators have different effects on gender related indicators in different countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation